2018
DOI: 10.1186/s12913-018-3279-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported hypertension in Northern China: a cross-sectional study of a risk prediction model and age trends

Abstract: BackgroundHypertension is a major risk factor for the global burden of disease, particularly in countries that are not economically developed. This study aimed to evaluate risk factors associated with self-reported hypertension among residents of Inner Mongolia using a cross-sectional study and to explore trends in the rate of self-reported hypertension.MethodsMulti-stage stratified cluster sampling was used to survey 13,554 participants aged more than 15 years residing in Inner Mongolia for the 2013 Fifth Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
1
31
1
Order By: Relevance
“…First, the finding that FIS was significantly associated with self-reported hypertension rather than a hypertension diagnosis or elevated measured blood pressure is an important finding. As others have noted, the reliability of self-reported hypertension can vary widely along patient demographic lines, with particularly high false positives found among people of low socioeconomic status [66,67]. Furthermore, the accuracy of self-reported health depends greatly on patients' level of healthcare access and health literacy [68].…”
Section: Discussionmentioning
confidence: 99%
“…First, the finding that FIS was significantly associated with self-reported hypertension rather than a hypertension diagnosis or elevated measured blood pressure is an important finding. As others have noted, the reliability of self-reported hypertension can vary widely along patient demographic lines, with particularly high false positives found among people of low socioeconomic status [66,67]. Furthermore, the accuracy of self-reported health depends greatly on patients' level of healthcare access and health literacy [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the overweight and obesity are the risk of hypertension. [17,18] Furthermore, hypertensive patients who normalized their body mass index can largely improve BP level and a number of metabolic and hormonal parameters. [19,20] Our study suggested that a major risk factor for hypertension among residents of Xinjiang is BMI ≥ 28.0, associated the highest addition to the risk score (23 points) of all of the risk factors examined, similar to several epidemiological research conducted in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Meeting one of the following conditions was considered to indicate hypertension. The first condition was self-reported hypertension; that is, having a diagnosis of hypertension and currently receiving hypertension treatment [13]. The second condition was field-measured hypertension, assessed as the average of three blood pressure measurements carried out by trained investigators and defined as average systolic blood pressure ≥ 140 mmHg and/or average diastolic blood pressure ≥ 90 mmHg.…”
Section: Definition Of Hypertensionmentioning
confidence: 99%
“…The prevalence of hypertension is higher in Inner Mongolia, however, the rate of awareness, treatment, and control are lower, which leads to the patients suffering from hypertension tend to be younger [12]. Because of respectively backward economic development, the level of culture and education are generally lower than other areas of the country, the level of medical care is poor, and residents lack awareness of health care, leading to poor public health conditions in terms of hypertension [13]. Therefore, hypertension has become a common chronic disease in people over 55 years old in Inner Mongolia [14].…”
Section: Introductionmentioning
confidence: 99%